ACINETOBACTER MAIN CAUSE OF HOSPITAL ACQUIRED INFECTIONS: A REVIEW - Nandi, Dinobandhu; Arjuna, Anania (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Hospital acquired infections (HAIs) are mostly caused by Gram-negative organisms and is one of the major issues in patient safety. These infections are often associated with the medical processes of hospitals such as invasive medical devices and various surgical procedures. Gram-negative organisms account for most infections in the hospital environment because of their ability to acquire resistant against multiple antibiotics. Through different mechanisms including the synthesis of Î²- lactamases, overexpression of transmembrane efflux pump, loss of porins, synthesis of antibiotic modifying enzymes, target mutations, ribosomal mutation or modifications, mutations in lipopolysaccharide structure etc. these organisms have developed drug-resistant property and the genes encoded in plasmids play a vital role in developing the resistant. Among all Gram-negative bacteria, Acinetobacter baumannii is an emerging pathogen that accounts for about 80% of all reported infections. Although other species of Acinetobacter are also often associated with HAIs. Acinetobacter is non-motile, obligate aerobic Gram-negative coccobacillus and are ubiquitous free-living saprophytes in soil and water. It is commonly transmitted through medical devices such as ventilators, urinary catheters and other invasive devices in hospitals but its ability to colonize on the skin of individuals often increases the rate of transmission through person to person contact. Patients admitted to Intensive Care Unit (ICU) are at the major risk of getting infected by A. baumannii and these includes pneumonia/ ventilator associated pneumonia (VAP), bloodstream infections, wound abscesses, urinary tract infections etc. Â